Core microbiota drive functional stability of soil microbiome in reforestation ecosystems. (11th December 2021) - Jiao, Shuo; Chen, Weimin; Wei, Gehong
Abstract: Revealing the ecological roles of core microbiota in the maintenance of the functional stability of soil microbiomes is crucial for sustainable ecosystem functioning; however, there is a dearth of whole‐soil profile studies on the fundamental topic in microbial ecology, especially in the context of ecological restoration. Here, we explored whether core microbiota influence the temporal changes in the functional stability of soil microbiomes throughout the soil profile (i.e., soil depths of 0–300 cm) during natural succession in restored ex‐arable ecosystems, via high‐throughput amplicon and metagenomic sequencing. We revealed that core microbiota were essential for the maintenance of the functional stability of soil microbiomes in reforestation ecosystems. Specifically, the core taxa within one cluster of soil network, which had similar ecological preferences, had major contributions to functional stability. Reforestation significantly decreased the functional stability of soil microbiomes, which exhibited significant variations along the vertical soil profile in the reforested soils. Overall, the findings enhance our understanding of the factors driving functional stability in soil microbiomes, and suggests that core microbiota should be considered a key factor and integrated in policy and management activities targeting the enhancement and maintenance of functional stability and ecosystem sustainability in ecological restoration programs. Abstract : We revealed that core microbiota were essential for the maintenance of the functional stability of soil microbiomes throughout the soil profile (i.e., soil depths of 0–300 cm) during natural succession in restored ex‐arable ecosystems, via high‐throughput amplicon and metagenomic sequencing. Reforestation significantly decreased the functional stability of soil microbiomes, which exhibited significant variations along the vertical soil profile in the reforested soils. The results highlight the potential major role of soil core microbiota in the enhancement and maintenance of functional stability, which may require greater attention during ecological restoration activities in ex‐arable ecosystems in future.